Additional Conditions in Marriage Contracts in North Kalimantan: Between Local Wisdom and Legality of Islamic Law - Muh Evendi; Dul Jalil (Transpublika Publisher, 2026)
Marriage contracts are often accompanied by local phenomena in the form of additional requirements proposed by either party. The goal of the research is to analyze the additional Conditions in Marriage Contracts in North Kalimantan based on the legal Perspective, normative conflicts, and its impact to the socio legal aspect. This study employs a doctrinal legal approach (juridical-normative) to examine the validity of additional conditions in marriage contracts based legal materials including Law Number 1 of 1974, the Indonesia Civil Code (KUHPerdata), the Compilation of Islamic Law, and Government Regulation No. 9/1975. The result of the research is in the practice of including additional conditions in marriage contracts in North Kalimantan illustrates the profound impact of local wisdom. For example, the Bugis community enforces uang panai (dowry), several traditional rituals among the Bulungan community, and also Tidung cultural traditions. From a legal perspective, the additional conditions in marriage contracts should be viewed in light of Law No. 1 of 1974 on Marriage, Government Regulation No. 9 of 1975, Compilation of Islamic Law (KHI), and Civil Code or KUHPerdata. Conditions such as uang panai in Bugis tradition or symbolic rituals in Bulungan and Tidung communities may be recognized as cultural practices, but they do not carry binding legal force under civil law unless incorporated into a formal marriage agreement that complies with the provisions of KUHPerdata. Furthermore, additional requirements in a marriage contract not only impact the immediate couple involved but can also influence broader social dynamics.